Publication Trends and Hot Topics in Ethnoscience Research: A Bibliometric Study - Fadillah, Muhammad Aizri; Usmeldi, Usmeldi; Lufri, Lufri; Mawardi, Mawardi; Festiyed, Festiyed (Jurnal Ilmiah Wahana Pendidikan, 2025)
Ethnoscience, which integrates traditional knowledge with scientific approaches, is increasingly attracting attention in the academic community as a culture-based solution to various global challenges. This study aims to analyze publication trends and research topics in ethnoscience over the past decade (2014-2024) using a bibliometric approach. A total of 84 articles indexed in Scopus were analyzed to evaluate trends in the number of publications, geographical distribution, as well as hot topics based on keyword co-occurrence analysis. The results showed a significant increase in the number of publications and citations, with the largest spike in the 2019-2024 period. Indonesia became the country with the largest contribution (more than 50% of publications), followed by Brazil and the United States, which focused on exploring local traditions and interdisciplinary approaches, respectively. The topic analysis identified two main themes: critical thinking and problem-solving as the most recent focus and scientific literacy and context-based learning as the most cited themes. These findings suggest that ethnoscience is increasingly relevant in global research, especially in supporting culture-based education, sustainability and local innovation to face global challenges. This study recommends strengthening international collaborations and further exploration of the integration of ethnoscience with technology and environmental sustainability.